Semantic typology of Tuvan proverbs (empirical and axiological aspects) - Ivanov, Eugene Eu. (The New Research of Tuva, 2022)
One of the crucial tasks of contemporary paremiology as a separate linguistic discipline is a semantic description of proverbs and their classification into semantic types according to various criteria. The article examines the categorization of the semantics of Tuvan proverbs, differentiates and describes their semantic types according to the criterion “attitude to reality” in the empirical and axiological aspects.As a result of the study, it has been found that proverbs of the Tuvan language in terms of their content’s relation to extralinguistic reality can either contradict or be consistent with it in the empirical aspect. Proverbs, the content of which does not contradict reality, are divided into nomological and non-nomological, depending on the expression of necessary vs. accidental, essential vs. non-essential, regular vs. irregular connections between multiple objects. Proverbs that have no nomological content are classified into truistic and non-truistic in respect of the fact whether it is widely known vs. not well-known, stereotypical vs. original, evident vs. non-evident. In axiological terms, proverbs that do not have a truistic content express either essential or insignificant for the traditional worldview principles of reality. On this basis, they are differentiated into sentential and gregueric.
Keywords: paremiology; proverb; proverbial semantics; semantic typology; empirical aspect; axiological aspect; Tuvan language; Tuvan folklore